(untitled) (The Strategic Review for Southern Africa, 2020)
The East African Community (EAC) exemplifies the contradiction of independent Africa's efforts to champion regional integration and the idea of pan-Africanism, whilst maintaining the nation-state model left from colonialism. EAC I, 1967-1977, ultimately collapsed due to its inability to create a regional institutional framework that could supplant the nationalist tendencies of its member states' leaders; and failing to adopt a people-centred inclusive approach to its structure and actions. The resultant human security issues suffered throughout post-colonial East Africa at their essence have been caused by the victorious nationstate's continued failure to offer this inclusive citizenship to its peoples. Despite the EAC II's, 2001-present, espoused people-centred reincarnation, it too has so far failed to create the inclusive citizen, or peoplecentred approach to its development and so risks the continued insecurity of its people.